2020
DOI: 10.3390/w12092556
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Co-Digestion of Kitchen Waste and Blackwater for Different Practical Application Scenarios in Decentralized Scale: From Wastes to Energy Recovery

Abstract: This study was performed to investigate the anaerobic digestion feasibility of kitchen waste and blackwater under different scenarios in laboratory tests. According to biochemical methane potential tests, when the kitchen waste to blackwater solid ratio was 1:1, the cumulative methane production reached the highest amount at 313.2 mL/g volatile solids (VSs), which was 26.4% and 29.4% higher than the anaerobic monodigestion of kitchen waste and blackwater, respectively, indicating that the anaerobic codigestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Though the degradation efficiency at 12% TS content was higher than at 15% TS, the biogas production was higher at 15% TS. Similar results were obtained by Wang et al (2020aWang et al ( , 2020b, which reported higher degradation efficiency but lower biogas yield at 5% TS than at 15% TS. Yi et al (2014) also found that high TS content lower than 20% has a positive impact on methane yield.…”
Section: Specific Biogas and Methane Production For Different Tssupporting
confidence: 86%
See 1 more Smart Citation
“…Though the degradation efficiency at 12% TS content was higher than at 15% TS, the biogas production was higher at 15% TS. Similar results were obtained by Wang et al (2020aWang et al ( , 2020b, which reported higher degradation efficiency but lower biogas yield at 5% TS than at 15% TS. Yi et al (2014) also found that high TS content lower than 20% has a positive impact on methane yield.…”
Section: Specific Biogas and Methane Production For Different Tssupporting
confidence: 86%
“…Little difference in findings was may be due to the substrate characteristics and the conditions under which the experiments were performed. The methane production in this study (33.82-78.12 L/kg VS) was much less than the previous study (247 L/kg VS) (Wang et al 2020a(Wang et al , 2020b. The difference was may be due to different substrate composition or different experimental condition.…”
Section: Specific Biogas and Methane Production For Different Tscontrasting
confidence: 72%
“…The modified Gompertzian model 34 was employed to fit the cumulative methane yield curves for each pretreatment group during batch anaerobic digestion to obtain the maximum CH 4 production potential ( P ), CH 4 production rate ( R ), and lag phase ( λ ) as shown in eqn (5) M = P × exp{−exp[( R × e )/ P × ( λ − t ) + 1]} where M is the cumulative CH 4 production (mL per gVS added ) over time t (day), P is the maximum CH 4 potential (mL per gVS added ), R is the maximum CH 4 production rate (mL per gVS added per d), λ is the lag phase (day) and ‘ e ’ is exp(1) = 2.71828. The three parameters P , R , and λ were obtained by the nonlinear fit program in Origin 2021.…”
Section: Methodsmentioning
confidence: 99%
“…BW can also be anaerobically co-digested with kitchen waste or other organic matter to improve the efficiency of biogas production (Gunnarsdóttir et al, 2014;Rajagopal et al, 2014;Hertel et al, 2015;Wang et al, 2020). The microbial community dynamics and inhibition effects of anaerobic digesters on BW have also been investigated (Gao et al, 2019a;Gao et al, 2019b).…”
Section: Anaerobic Digestionmentioning
confidence: 99%